Hybrid professionals: new configurations of teacher professionalism in the neoliberal political context - Javier Molina-Pérez; Julián Jesús Luengo Navas (FahrenHouse, 2021)
The teaching profession occupies a central space in contemporary debates in the field of educational policy. This article aims to understand the transformations that teaching professionalism may be experiencing as a consequence of the demands posed by the political practices of the New Public Management (NPM). For this, it is used a qualitative methodological approach that combines the theories of the participants, the theories of the researchers and the existing formal theories. Concreted in an inductive method, the proposal of the Grounded Theory is followed. As an information gathering technique, the qualitative interview is used. Sixteen have been the participants of the research: four directors and twelve teachers. The information has been analyzed with the QSR NVivo12 software. The results show that teachers' work is being reconfigured. It is evident that neoliberal practices are modifying professional logic. The teaching staff manifests an excess of control and distrust that makes the work more uncomfortable and affects health problems arising from the stress they report suffering. Contradictions are experienced between professional convictions and the imperatives proposed by the NPM, which transform teachers into an «executing technician». In this sense, new ways of managing tensions are evidenced through spaces of professional resistance and «adaptations» to the demands of neoliberal agenda. This suggests that the traditional dichotomy between occupational and organizational professionalism may be blurring, leading to new professional approaches based on hybrid skills.